Kinetics, safety and tolerability of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate in healthy adult subjects - Clarke, Kieran; Tchabanenko, Kirill; Pawlosky, Robert; Carter, Emma; Todd King, M.; Musa-Veloso, Kathy; Ho, Manki; Roberts, Ashley; Robertson, Jeremy; VanItallie, Theodore B.; Veech, Richard L. (Regulatory toxicology and pharmacology, 2012)
► d-β-hydroxybutyrate-(R)-1,3-butanediol was given as a drink to healthy adults. ► Blood ketones were elevated, but the ketone monoester was not detected. ► The ketone monoester was well tolerated. ► Ingestion of the ketone monoester is a safe and viable way to elevate blood ketone concentrations. Induction of mild states of hyperketonemia may improve physical and cognitive performance. In this study, we determined the kinetic parameters, safety and tolerability of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate, a ketone monoester administered in the form of a meal replacement drink to healthy human volunteers. Plasma levels of β-hydroxybutyrate and acetoacetate were elevated following administration of a single dose of the ketone monoester, whether at 140, 357, or 714mg/kg body weight, while the intact ester was not detected. Maximum plasma levels of ketones were attained within 1–2h, reaching 3.30mM and 1.19mM for β-hydroxybutyrate and acetoacetate, respectively, at the highest dose tested. The elimination half-life ranged from 0.8–3.1h for β-hydroxybutyrate and 8–14h for acetoacetate. The ketone monoester was also administered at 140, 357, and 714mg/kg body weight, three times daily, over 5days (equivalent to 0.42, 1.07, and 2.14g/kg/d). The ketone ester was generally well-tolerated, although some gastrointestinal effects were reported, when large volumes of milk-based drink were consumed, at the highest ketone monoester dose. Together, these results suggest ingestion of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate is a safe and simple method to elevate blood ketone levels, compared with the inconvenience of preparing and consuming a ketogenic diet.